Use of a modified Delphi approach to develop research priorities in HPB surgery across the United Kingdom. Issue 11 (November 2019) - Knight, Stephen R.; Pathak, Samir; Christie, Alan; Jones, Louise; Rees, Jonathan; Davies, Hayley; Wilson, Michael S.J.; Vaughan-Shaw, Peter; Roberts, Keith; Toogood, Giles; Harrison, Ewen M.; Taylor, Mark A.
Abstract: Background: Research prioritisation can help identify clinically relevant questions and encourage high-quality, patient-centred research. Delphi methodology aims to develop consensus opinion within a group of experts, with recent Delphi projects helping to define the research agenda and funding within several medical and surgical specialties. Methods: All members of the Association of Upper Gastrointestinal Surgeons (AUGIS) were asked to submit clinical research questions using an online survey (Phase 1). Two consecutive rounds of Delphi prioritisation by multidisciplinary HPB healthcare professionals (Phase 2) were undertaken to establish a final list of the most highly prioritised research questions. A multidisciplinary steering committee analysed the results of each phase. Results: Ninety-three HPB-focussed questions were identified in Phase 1, with thirty-seven questions of sufficient priority to enter a further prioritisation round. A final group of 11 questions considered highest priority were identified. The most highly ranked research questions related to treatment pathways, operative strategies and the impact of HPB procedures on quality of life, particularly for malignant disease. Conclusion: Expert consensus has identified research priorities within the UK HPB surgical community over the coming years. Funding applications, to establish well-designed, high quality collaborative research are now required to address these questions.